PENAMBAHAN PROTEKSI OVERCURRENT RELAY UNTUK MENINGKATKAN KEANDALAN PENYULANG JETIS PADA GI WLINGI - Gymnastiar, Muhammad Ilham; Dhofir, Moch.; Hasanah, Rini Nur (Jurnal Mahasiswa TEUB, 2024)
The purpose of this study is to obtain the setting of the overcurrent relay (OCR) and the right coordination to protect the Jetis feeder network from 3-phase and 2-phase short-circuit current levels. The addition of OCR is also done on the Jetis Feeder to improve network reliability. To set OCR, it starts by calculating the 3-phase and 2-phase short-circuit currents in each protection zone based on the impedance of the equipment that supports each protection zone. The calculation of OCR settings uses the British BS-142 standard guideline with OCR working time using the IEC 60255-151:2009 standard with the OCR curve type standard inverse. ETAP software in the study was used to simulate short-circuit currents and also OCR work analysis. The output of the ETAP simulation is in the form of short-circuit current values for each protection zone and also the OCR working time curve of each protection zone. The result of this study is OCR resetting from the existing value that the OCR coordination condition of zone 1 and zone 2 is still overlapping. Therefore, OCR zone 1 and OCR zone 2 were reset with the TMS result in zone 1 being 0.4 and TMS zone 2 being 0.225. The trip time distance between zone 1 and zone 2 is 0.397s. The analysis of the addition of OCR in Zone 3 to improve reliability by sharing the load. The addition of OCR in zone 3 results in a TMS of 0.1. The trip time distance between zone 2 and zone 3 is 0.283s which is in accordance with the IEEE std 242-1986 standard for the working time limit between two relays is 0.2s-0.4s. Therefore, the delay time distance in zone 1, zone 2 and zone 3 relays has worked well according to existing protection guidelines. Keywords — Relay, Over Current Relay, time setting, current setting, Feeder, ETAP.